Tuberous sclerosis complex Esclerose tuberosa - Daniela Araujo Rodrigues; Ciro Martins Gomes; Izelda Maria Carvalho Costa (Sociedade Brasileira de Dermatologia, 2012)
Tuberous Sclerosis Complex, also known as Epiloia or Bourneville-Pringle disease is an autosomal dominant neurocutaneous syndrome with variable clinical expression. It is a multisystem disorder that may be associated with hamartomas in multiple organs in an unpredictable manner. The dermatologist plays an essential role in the history of the disease, since skin manifestations represent the most prevalent clinical features, enabling early diagnosis and intervention in its natural course. This article aims to inform the scientific community about advances made in the study of genetics and molecular biology. Recent findings regarding stimulation of tumor growth have been changing the history of this condition, making therapeutic trials with topical and systemic drugs possible. Knowledge of these topics enables better management of the patients affected, since tissue replacement by tumors can result in significant morbidity and mortality. A Esclerose Tuberosa, também conhecida como Epilóia ou Facomatose de Pringle-Bourneville, é uma síndrome neurocutânea de caráter autossômico dominante com expressões clínicas variadas. É uma doença multissistêmica que pode cursar com hamartomas em diversos órgãos, de forma imprevisível. O dermatologista tem papel essencial na história da doença, uma vez que as afecções cutâneas representam as mais prevalentes apresentações clínicas, possibilitando assim o diagnóstico precoce da síndrome e intervenção na sua evolução natural. O presente artigo tem o objetivo de atualizar a comunidade científica sobre avanços alcançados no estudo genético e biologia molecular. Recentes descobertas sobre o estímulo do crescimento tumoral vêm mudando a evolução desta patologia, possibilitando ensaios terapêuticos com drogas tópicas e sistêmicas. O conhecimento destes aspectos possibilita melhor condução dos pacientes acometidos, dado que a substituição tumoral dos diversos tecidos pode resultar em relevante morbidade e mortalidade.